The State and Perspectives of the World Population Aging Process - Murkowski, Radosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
The aging of the population is the process of increasing the proportion of older people in the population, which is the result of two long‑term demographic trends: a decrease in fertility and an increase in life expectancy. For the correct measurement of the advancement of this process, it is extremely important what age we consider the beginning of the old age. In the traditional approach older people are most often considered to be people over 60 or 65 years of age. In the alternative approach the beginning of the old age can be considered the age which the expected life expectancy is exactly 15 years. In many parts of the world, the phenomenon of depopulation may appear in the coming years, and the number of children will be lower than the number of older people. In the future, older people will be in nearly one third of their entire population in many regions. However, the percentage of people who have 15 or fewer years to live will stabilize in the future at about 15% of the total population in the most developed countries. Therefore, the beginning of the old age will grow in the future up to 70 years and more in the most developed countries.